2020
DOI: 10.1111/1759-7714.13433
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin‐targeted PD‐L1 in lung cancer growth inhibition

Abstract: Background: Aspirin is a classic anti-inflammatory drug and its anticancer effect has been previously explored in many types of cancer including colorectal cancer therapy. Programmed cell death-ligand 1 (PD-L1) is widely expressed in tumor cells and displays an inhibitory role in antitumor immunity. This study aimed to clarify the role of PD-L1 in aspirin-suppressed lung cancer. Methods: The inhibitory effect of aspirin on lung cancer cell proliferation was assessed using an MTT cell viability assay. The role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
1
16
1
Order By: Relevance
“…As was noted before, in vitro studies suggested a synergic effect of adding NSAID/ASA to PD-1/ PD-L1 inhibitors for a better anti-cancer effect [5][6][7]. More specifically, researchers found that ASA suppressed the growth of cancer cells, including lung cancer cells, via inhibiting PDL-1 overexpression [14][15]. Those findings could explain our suggested clinical benefit of using ASA in NSCLC patients at biochemical and histological levels, especially with PD-L1 inhibitors.…”
Section: Variablessupporting
confidence: 67%
“…As was noted before, in vitro studies suggested a synergic effect of adding NSAID/ASA to PD-1/ PD-L1 inhibitors for a better anti-cancer effect [5][6][7]. More specifically, researchers found that ASA suppressed the growth of cancer cells, including lung cancer cells, via inhibiting PDL-1 overexpression [14][15]. Those findings could explain our suggested clinical benefit of using ASA in NSCLC patients at biochemical and histological levels, especially with PD-L1 inhibitors.…”
Section: Variablessupporting
confidence: 67%
“…Aspirin suppresses platelet-associated invasion of OC cells [ 20 ]. Moreover, a recent study reports that aspirin inhibits lung cancer cell growth by regulating the TAZ/PD-L1 signaling [ 21 ], presenting the effect of aspirin on PD-L1 in lung cancer. Our data indicated that treatment with aspirin suppressed the OC cell proliferation in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, cell-based analyses also showed that increasing doses of aspirin reduced the cancer cell viability along with long-term clonogenesis while affecting caspase-3 activity minimally (Der et al 2020 ). Besides, Zhang et al ( 2020a , b ) showed that aspirin reduced the protein levels of programmed cell death-ligand 1 (PD-L1) which is expressed in tumor cells and displays an inhibitory role in antitumor immunity in A549 and H1299 human lung cancer cell lines. Further, the promoter of PD-L1 was cloned in a luciferase reporter pGL3-basic plasmid and aspirin was shown to reduce luciferase activity of pGL3-PD-L1.…”
Section: The Origin and Development Of Nsaids: A Journey To The Pastmentioning
confidence: 99%